Heterotopic Ossification after Direct Anterior Approach Total Hip Arthroplasty - Cohen, Eric M.; Babu, Jacob M.; Ritterman, Scott; Tuttle, John; Eisenson, Daniel; Rubin, Lee E. (The Journal of Hip Surgery, 2019)
Previous studies have demonstrated varying rates of heterotopic ossification (HO) after total hip arthroplasty (THA) depending on which anatomical approach is utilized. The direct anterior approach (DAA) is considered to be a muscle-sparing approach to the hip, which may lead to decreased rates of HO formation. This study evaluated the incidence of HO formation after DAA THA. The current work is a retrospective review of patients who underwent DAA THA. Six-month postoperative radiographs were evaluated and HO grade was classified using the Brooker classification system. Baseline characteristic differences between the Brooker classification groups were analyzed, specifically looking at: age, sex, type of deep venous thrombosis prophylaxis utilized, and preoperative Bombelli arthritis type. The overall incidence of HO in this DAA group was 179/485 patients (36.9%). There were 14 patients (2.9%) with Brooker Type 3 HO and 1 patient (0.21%) with Brooker Type 4 HO. No surgical excision of HO was performed. Patients were significantly more likely to develop HO if they had Bombelli hypertrophic arthritis (p < 0.00003). Preoperative radiographic imaging suggesting Bombelli hypertrophic arthritis is predictive of HO formation, warranting consideration for HO prophylactic treatment. The radiographic incidence of HO in DAA THA was 36.9%, which is within the previously reported range of HO seen for lateral and posterior approaches to the hip. HO after total hip arthroplasty is likely due to soft tissue handling, hemostasis, and patient factors, rather than type of surgical approach.
Keywords: Bombelli arthritis; Brooker classification; direct anterior approach; heterotopic ossification; total hip arthroplasty